问题 解答题
9
4
11
-1
1
3
-4
2
3
2
3
×
4
15
+
2
3
×
11
15
(5.52÷0.6-8.6)×1.5;
3
4
-
2
3
×(
5
8
-
1
2
);
(6
1
2
-5
3
10
)×(7-4
1
3
);
1
5
÷[(
1
6
+
5
18
)×
3
5
].
答案

(1)9

4
11
-1
1
3
-4
2
3

=9

4
11
-(1
1
3
+4
2
3

=9

4
11
-6

=3

4
11

(2)

2
3
×
4
15
+
2
3
×
11
15

=

2
3
×(
4
15
+
11
15

=

2
3
×1

=

2
3

(3)(5.52÷0.6-8.6)×1.5

=(9.2-8.6)×1.5

=0.6×1.5

=0.9;

(4)

3
4
-
2
3
×(
5
8
-
1
2

=

3
4
-
2
3
×
1
8

=

3
4
-
1
12

=

2
3

(5)(6

1
2
-5
3
10
)×(7-4
1
3

=

6
5
×
8
3

=

16
5

(6)

1
5
÷[(
1
6
+
5
18
)×
3
5
]

=

1
5
÷[
4
9
×
3
5
]

=

1
5
÷
4
15

=

3
4

选择题
单项选择题